The Reformulation of Government Regulations in Lieu of Law: Constitutional Court's Decision Perspective - Habib Al Huda; I Made Halmadiningrat; Gio Arjuna Putra; Anak Agung Arumi Jayanti Kusumasari (University of Jember, Indonesia, 2023)
The President's issuance of Regulations in Lieu of Law No 1 of 2022 regarding the Job Creation represents a deliberate endeavor to operationalize and further refine the previously ratified Job Creation Law. The objective of this research is to provide a lucid comprehension of the formulation of the Regulations in Lieu of Law that adheres to the Constitutional Court's directives. This paper employs normative legal research methodologies, incorporating conceptual, historical, statutory, and jurisprudential analyses to scrutinize extant legal quandaries concerning the urgency and constitutionality of Regulations in Lieu of Law No 1 of 2022 regarding the Job Creation. Furthermore, the research yields the proposition that the promulgation of Government Regulation in Lieu of Law No. 1 of 2022 on Job Creation, vis-Ã -vis Constitutional Court Decision No. 91/PUU-XVIII/2020, may be regarded as a departure from the constitutional imperatives articulated in Constitutional Court Decision No. 91/PUU-XVIII/2020. Furthermore, concerning the reformulation of provisions governing the issuance of a Regulation in Lieu of Law by the President within the national legislative framework, a predicated state of emergency is a requisite antecedent. The President is obligated to communicate this state of emergency to the Indonesian People's Consultative Assembly and the public before promulgating the Regulation in Lieu of Law.